2003
DOI: 10.1089/152581603322023089
|View full text |Cite
|
Sign up to set email alerts
|

No Differences in Colony Formation of Peripheral Blood Stem Cells Frozen with 5% or 10% Dimethyl Sulfoxide

Abstract: High-dose chemotherapy with autologous stem cell rescue usually requires cryopreservation of the cells. For several years, 10% dimethyl sulfoxide (DMSO) has been used as the standard cryoprotectant. Because DMSO infusion can lead to toxic clinical complications in a dose-related manner, we wanted to evaluate if reduction to 5% DMSO would be possible. We have compared colony formation in the myeloid, erythropoietic, and megakaryocyte lineages in peripheral blood progenitor cell (PBPC) samples cryopreserved in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 17 publications
3
40
0
1
Order By: Relevance
“…Recently, there have been several reports suggesting that cells can be successfully cryopreserved with minimal concentrations of DMSO [39][40][41][42][43][44][45][46][47][48][49][50][51]. For example, Zhao et al [46] showed that the use of 5% or 10% DMSO in combination with either 20% or 70% serum produced similar results during cryopreservation of fetal human liver CD34 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been several reports suggesting that cells can be successfully cryopreserved with minimal concentrations of DMSO [39][40][41][42][43][44][45][46][47][48][49][50][51]. For example, Zhao et al [46] showed that the use of 5% or 10% DMSO in combination with either 20% or 70% serum produced similar results during cryopreservation of fetal human liver CD34 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the published literature over the past several years identifies several reports suggesting that adult stem cells (hematopoietic and non-hematopoietic) can be successfully cryopreserved with minimal concentrations of DMSO. 45,[52][53][54][55][56][57][58][59][60][61][62] For example, Zhao et al 57 showed that the use of 5 or 10% DMSO produced similar results during cryopreservation of fetal human liver CD34 + cells. Sputtek et al 60 reported optimal cryopreservation of peripheral blood HPCs using at least 5% DMSO.…”
Section: Clinical Banking Of Adipose Derived Adult Stem Cells (Ascs)mentioning
confidence: 99%
“…It has been suggested that lowering the dose of DMSO may be advisable. Lower concentrations, for example 5% DMSO 16,17 or 3.5% DMSO 18 are an effective cryoprotectant. Stem cell washing to remove DMSO appears to have no adverse effect on haematological recovery and may reduce toxicity 19 and fractionation of stem cell administration may similarly reduce side effects.…”
Section: Dimethyl Sulfoxidementioning
confidence: 99%